Acoustic Emission Diagnostics of the Destruction of Welded Joints Stainless Steel Pipes Arising Welding; Applied Mechanics and Materials; Vol. 770 : Urgent Problems of Up-to-Date Mechanical Engineering - Apasov A. M. Aleksandr Mikhailovich (Materials Science in Mechanical Engineering, 2015)
Title screen